2020
DOI: 10.21203/rs.2.18053/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of Nontuberculous Mycobacteria in a Tertiary Hospital in Beijing, China, January 2013 to December 2018

Abstract: Background To investigate the species distribution of non-tuberculous mycobacteria (NTM) among tuberculosis (TB) specimens collected from January 2013 to December 2018 at Peking Union Medical Hospital (Beijing), China. NTM species identification was carried out by DNA microarray chip. Results Mycobacterial species were detected in 1514 specimens from 1508 patients, among which NTM accounted for 37.3% (565/1514), increasing from a proportion of 15.6% in 2013 to 46.1% in 2018 ( P <0.001). Among the 565 NTM po… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Strains belonging to the M. abscessus complex (n=58, 41.43%) were the most frequently isolated NTM in the Nanshan District and were also the most common in the Guangzhou area of southern China [24]. In contrast, studies in other areas of China, such as Beijing (north) [25], Changchun (northeast) [26], Nanjing (southeast) [27] found that M. intracellulare was the most common NTM species isolated from patient specimens. In our study, isolates belonging to the MAC (n=41, 29.29%), were the second most common group of NTM species identi ed, and included M. avium (n=13, 9.29%), M. intracellulare (n=13, 9.29%), M. colombiense (n=5, 3.27%), M. marseillense (n=5, 3.27%), M. chimaera (n=4, 2.86%) and M. paraintracellulare (n=1, 0.71%).…”
Section: Discussionmentioning
confidence: 99%
“…Strains belonging to the M. abscessus complex (n=58, 41.43%) were the most frequently isolated NTM in the Nanshan District and were also the most common in the Guangzhou area of southern China [24]. In contrast, studies in other areas of China, such as Beijing (north) [25], Changchun (northeast) [26], Nanjing (southeast) [27] found that M. intracellulare was the most common NTM species isolated from patient specimens. In our study, isolates belonging to the MAC (n=41, 29.29%), were the second most common group of NTM species identi ed, and included M. avium (n=13, 9.29%), M. intracellulare (n=13, 9.29%), M. colombiense (n=5, 3.27%), M. marseillense (n=5, 3.27%), M. chimaera (n=4, 2.86%) and M. paraintracellulare (n=1, 0.71%).…”
Section: Discussionmentioning
confidence: 99%